1981
DOI: 10.1001/archpedi.1981.02130250036012
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Mediated Immune Responsiveness to Measles

Abstract: Studies of cell-mediated immunity (CMI) to measles were carried out in patients with natural measles infection, in recipients of live measles vaccine, and in umbilical cord blood specimens from infants of mothers who were seropositive for measles. Evidence of CMI to measles was found in 100% of patients with natural infection but in only 62% of vaccine recipients and, interestingly, in 40% of umbilical cord blood specimens. Eight of these infants were subsequently studied at 4 to 5 months of age, at which time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The stimulation index (SI) was cal-culated as the mean counts per minute (cpm) in measles antigen-stimulated wells divided by the mean cpm in control wells. A positive SI to measles was !3.0 [Gallagher et al, 1981;Linnemann et al, 1982;Ward et al, 1995;Gans et al, 1998Gans et al, , 2001. Phytohemagglutinin (PHA) (Difco, Detroit, MI) was used as a positive control.…”
Section: T-cell Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulation index (SI) was cal-culated as the mean counts per minute (cpm) in measles antigen-stimulated wells divided by the mean cpm in control wells. A positive SI to measles was !3.0 [Gallagher et al, 1981;Linnemann et al, 1982;Ward et al, 1995;Gans et al, 1998Gans et al, , 2001. Phytohemagglutinin (PHA) (Difco, Detroit, MI) was used as a positive control.…”
Section: T-cell Proliferation Assaymentioning
confidence: 99%
“…When proliferation of T cells stimulated with measles antigen is used to assess cellular immunity against measles, memory responses have been reported in 100% of individuals who had natural measles infection and from 62-89% in children who received the live attenuated measles vaccine [Gallagher et al, 1981;Gans et al, 1998Gans et al, , 2001Pabst et al, 1999]. The effect of a second dose of measles vaccine on cellular immunity in adults has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-mediated immunity (CMI) is of crucial importance to measles immunity and can be assessed by measuring CTL, lymphoproliferative and cytokine responses [13]. Memory T lymphocyte proliferative responses to measles antigens have been reported in 100% of individuals who had natural measles infection and in approximately 60% to 90% of immunized children [14][15][16]. Although we have reported associations between low antibody levels and specific HLA alleles, associations between cellular (proliferative) immune responses elicited by MV and by naturally processed measles-derived peptides have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…As the peak incidence of RS virus bronchiolitis is at 2-3 months of age, the presence of sensitised lymphocytes at this time could be due to transplacental transfer of cellular reactivity. A number of reports have suggested that cord blood lymphocytes 'may be sensitised to a range of viral antigens including measles, vaccinia, herpes, and influenza A [Russell, 1975;Gallagher et al, 1981;Ruben and Thompson, 19811.…”
Section: Introductionmentioning
confidence: 99%
“…As the peak incidence of RS virus bronchiolitis is at 2-3 months of age, the presence of sensitised lymphocytes at this time could be due to transplacental transfer of cellular reactivity. A number of reports have suggested that cord blood lymphocytes 'may be sensitised to a range of viral antigens including measles, vaccinia, herpes, and influenza A [Russell, 1975;Gallagher et al, 1981;Ruben and Thompson, 19811. Evidence for the transplacental transfer of cellular reactivity to RS virus has been reported by Sieber and his colleagues [1977] and in a previous report from this laboratory [Scott et al, 19811, although the frequency of responses in cord blood cell cultures differed in the two studies. Therefore, in the present study we have examined a larger series of cord blood samples, in order to determine the exact frequency of this response to RS virus, with a view to determining its role in the development of RS virus disease in infancy.…”
Section: Introductionmentioning
confidence: 99%